The relationship between workload, job stress, nutritional status, and shift work the night with the fatigue of nurses working in hospitals Aceh Singkil 2020 - Yuliani, Riski; Ginting, Chrismis Novalinda; Chiuman, Linda; Girsang, Ermi (International Journal of Research in Medical Sciences, 2021)
Background: Work fatigue is a subjective feeling accompanied by a decrease in efficiency and a need for work. In the initial survey at RSUD Aceh Singkil 40% nurses with heavy workloads and 60% with moderate workloads, 80% with heavy stress and 20% with moderate stress, 20% nurses with good nutrition and 80% of the people are not well, 80% of nurses are tired and 20% are not tired, 70% of nurses are tired and 30% are moderate. The aim of the study was to identify the relationship between workload, work stress, nutritional status, and night shifts with the work fatigue of nurses at RSUD Aceh Singkil. Methods: The type of research used was quantitative research using an analytical approach and a cross sectional study design. The population in this study were all nurses in the inpatient installation who served in the Aceh Singkil Regional Hospital and were not structural nurses. Results: Determination of the sample using a total sampling technique, where the sample taken is all nurses who served in the inpatient installation of RSUD Aceh Singkil, namely 170 nurses. In the results obtained by Chi square analysis, the relationship between workload and work fatigue with a p value of 0, 000<α, then H0 was rejected, which means that there was a relationship between variables, work stress and work fatigue p value 0, 000<α, then H0 was rejected, which means there was a relationship. Between variables, nutritional status and work fatigue p value 0.000<α, so H0 was rejected, which means there was a relationship between variables, night work shift and work fatigue p value 0.000 <α then H0 was rejected, which means there is a relationship between variables. Conclusions: From the results, it can be concluded that there is a significant relationship between workload, work stress, nutritional status, and night work shifts with the work fatigue of nurses at RSUD Aceh Singkil.